Latvių bendrinės kalbos vietos prieveiksmių semantinė struktūra - Davulienė, Gintarė (Baltistica, 2006)
SEMANTIC STRUCTURE OF STANDARD LATVIAN ADVERBS OF PLACE This is a description of the semantic structure of standard Latvian adverbs of place. It starts with a paradigmatic analysis (first, a reference is made to determinations of the adverbs of place, which are provided by Latviešu literārās valodas vārdnīca; then an orientation meaning is defined, followed by marking of the integral and differential features, and determination of semantic oppositions), later followed by a syntagmatic analysis. In analyzing the structure of the adverbs of place within the syntagmatic approach, it is necessary to consider a context and a situation. Analysis of paradigmatic and syntagmatic relations underlie the classification of the adverbs of place. On the basis of this classification, differential features that are the least significant elements are being identified. 24 pairs of differential features can be used to describe the semantic structure of the adverbs of place. When the system of paradigmatic relations of all the adverbs of place is fully described, it is possible to characterize every single adverb of place as a particular combination of these features, and to set its place in this system. For instance, the adverb of place klāt can be characterized as [non-interrogative – non-cognitive – non-deictic – non-vertical – non-inside – side – non-concrete], etc.